2022
DOI: 10.3390/v14102097
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Protection from Vaccinating Children against Influenza A Virus Infection in Households

Abstract: Influenza vaccination is an important intervention to prevent influenza virus infection. Our previous analysis suggested that indirect protection is limited in an influenza B epidemic in Hong Kong. We further analyzed six influenza A epidemics to determine such potential. We applied a statistical model to estimate household transmission dynamics in the 3 influenza A(H3N2) and 3 pandemic influenza A(H1N1) epidemics. Then, we estimated the reduction in infection risk among unvaccinated household members when all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…Despite these uncertainties, high rates of vaccination are thought to reduce community burden of influenza: A retrospective study examining the impact of mandatory influenza vaccination in school-age children in Japan concluded that herd immunity in this age group prevented ∼40,000 deaths annually (148). In another study focused on household transmission, vaccination of one child per household was estimated to bring about a 10-20% reduction in cases (149).…”
Section: Vaccinationmentioning
confidence: 99%
“…Despite these uncertainties, high rates of vaccination are thought to reduce community burden of influenza: A retrospective study examining the impact of mandatory influenza vaccination in school-age children in Japan concluded that herd immunity in this age group prevented ∼40,000 deaths annually (148). In another study focused on household transmission, vaccination of one child per household was estimated to bring about a 10-20% reduction in cases (149).…”
Section: Vaccinationmentioning
confidence: 99%